2020
DOI: 10.1182/bloodadvances.2018027870
|View full text |Cite|
|
Sign up to set email alerts
|

WASP and Mst1 coregulate B-cell development and B-cell receptor signaling

Abstract: Mst1 is a serine/threonine kinase involved in cell survival, proliferation, apoptosis, and tumorigenesis. In mice, Mst1 regulates actin dynamics required for T-cell adhesion and migration, which correlate with thymic egress and entry into lymphatic tissue. The role of Mst1 in B cells and how it may control actin-dependent processes has not been well characterized. Wiskott-Aldrich syndrome protein (WASP) deficiency only moderately affects development and B-cell receptor (BCR) signaling, suggesting WASP likely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…MST1 regulates cytoskeletal microtubule dynamics and promotes F‐actin polymerisation 29 and also modulates BCR to induce actin remodelling by attaching WASP 30 . In the absence of CCR2, the levels of pMST1, pWASP and DOCK8 were increased after sAg stimulation (Figures 4L and S7J–M).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…MST1 regulates cytoskeletal microtubule dynamics and promotes F‐actin polymerisation 29 and also modulates BCR to induce actin remodelling by attaching WASP 30 . In the absence of CCR2, the levels of pMST1, pWASP and DOCK8 were increased after sAg stimulation (Figures 4L and S7J–M).…”
Section: Resultsmentioning
confidence: 96%
“…Consistent with the augmented F-actin accumulation, the MST1 regulates cytoskeletal microtubule dynamics and promotes F-actin polymerisation 29 and also modulates BCR to induce actin remodelling by attaching WASP. 30 In the absence of CCR2, the levels of pMST1, pWASP and DOCK8 were increased after sAg stimulation (Figures 4L and S7J-M). After pre-treatment with MST1 inhibitor, XMU-MP-1, the increased expression of pmTOR, pAKT, pS6 and DOCK8 in Ccr2-KO B cells were rescued (Figure 4M).…”
Section: Ccr2 Deficiency Promotes Mst1-regulated F-actin Accumulation...mentioning
confidence: 93%
“…The cytoskeletal defects of megakaryocytes are responsible for the low number of platelets in patients with WAS ( 92 ). WASP deficiency promotes T-cell cytoskeletal tension decay and phosphorylation of a serine/threonine protein kinase 4 (STK4) that usually increase T-cell migration, therefore promoting immune synapse breaking and secondary B cells dysfunction ( 93 , 94 ). WASP-deficient lymphocytes fails to differentiate into memory cells ( 95 ) and are more prone to develop DNA damages due to the loss of the Golgi-dispersal response, a recently described mechanism of cell survival after ionized radiation exsposure ( 96 ).…”
Section: Introductionmentioning
confidence: 99%
“…For cell development, the latest studies revealed that the interaction between WASp and other signaling molecules facilitates B cell development and movement. Mst1 and WASp are significant for central and peripheral development of B cells and can adjust mutual localization and function ( 293 ). Deficiency of DOCK2 reduces the activation of WASp and accelerates its degradation, causing dysfunction of actin accumulation and affecting the early activation process of B cells ( 294 ).…”
Section: Functions In Lymphocytesmentioning
confidence: 99%